Description of Food Intake and Physical Activity Related to The Event of Obesity in Adolescent Ages 16-18 Years Old - Juliana Putri; Yuwono Setiadi (Eduvest - Journal of Universal Studies, 2022)
Obesity is a health problem caused by excessive fat accumulation which causes a person to gain weight far above normal. Adolescence is also a period that is vulnerable to obesity, because in adolescence biological, psychosocial and cognitive changes begin to occur which begin during puberty and have a direct effect on the nutritional status and needs of adolescents. Unexpected health problems occur around the world which have resulted in a pandemic, namely the Covid-19 pandemic. This pandemic has changed several habits that can lead to health problems, namely the occurrence of being overweight above normal as happened to teenagers in the Sendangmulyo Village area. To find out the description of food intake and physical activity related to the incidence of obesity in adolescents aged 16-18 years in Sendangmulyo Village during the Covid-19 pandemic. Included in the nutritional research field of society using a cross sectional approach. The sample used in the study was 35 teenagers who live in Sendangmulyo Village. Intake data was collected twice 24 hours using the recall method and physical activity data was collected once by filling out a questionnaire. Most respondents have overweight nutritional status as many as 16 people (42.9%) with adequate energy intake (40%), with sufficient protein adequacy (45.7%), excess fat adequacy (60%) carbohydrate adequacy which is still lacking (57.1%) accompanied by low activity (54.3%). The majority of respondents have overweight nutritional status with sufficient energy and protein, but fat adequacy is still classified as excess, carbohydrate adequacy is still lacking and physical activity is still classified in the low category.